Scenario-Based analysis of energy transition for an outermost EU Territory: The case of Tenerife island - Santiago Escamilla-Fraile; Rubén Lorenzo Cruz-González; Oscar García-Afonso; Francisco J. Calero-García; Benjamín González-Díaz; Francisco J. Ramos-Real (Energy Conversion and Management: X, 2025)
The Canary Islands are targeting full decarbonization by 2040, a decade ahead of Spain and the European Union. However, the region relies heavily on aging fossil-fuel plants and energy imports, with only 20% of its electricity derived from renewable sources. This study evaluates official regional decarbonization plans’ feasibility and economic efficiency and proposes an alternative energy transition pathway tailored to Tenerife’s unique geographical and technical challenges. Using EnergyPLAN simulation software, three scenarios are modeled: the current trajectory, the implementation of regional decarbonization plans, and a novel pathway to achieve net-zero emissions by 2040. The proposed scenario achieves 86% renewable electricity generation and reduces electricity costs by 48%, from 0.56 to 0.29 €/kWh, outperforming official plans. Key strategies include introducing natural gas as a transitional fuel, deploying battery storage to support renewable energy expansion, and integrating offshore wind and green hydrogen technologies. This study advances energy transition research for isolated territories by offering practical, cost-effective solutions that balance feasibility and ambition with broader applicability to other land-constrained systems and outermost regions in Europe.